2015
DOI: 10.3892/ijo.2015.3001
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of new tumor cell properties by MSC-derived exosomes

Abstract: Interaction between multi-functional mesenchymal stroma/stem cells (MSC) and human tumor cells involves the exchange of biological material via extracellular vesicles including exosomes. Protein analysis of MSC-derived exosomes demonstrated the presence of MMP-2 and MSC-specific markers including CD90 and ecto-5'-nucleotidase (CD73). Incubation of tumor cells with these membranous particles revealed a rapid uptake of MSC-released microvesicles whereby breast cancer cells incorporated ~19% and SCCOHT-1 cells re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 27 publications
5
90
0
Order By: Relevance
“…Whereas exosomes are defined as small homogeneous membrane particles of endocytic origin ranging in size from 40 to 100 nm, microvesicles are directly shed from the plasma membrane into the extracellular environment representing a larger and heterogeneous population with 50 to 1000 nm in diameter [49]. Although both types of microparticles differ in size, origin and releasing mechanism, exosomes and microvesicles contain a large panel of proteins, functional mRNAs and regulatory microRNAs (miRs) which contribute to the cellular interplay between MSC and cancer cells within the tumor microenvironment and thereby altering the functionality of recipient cells [37]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas exosomes are defined as small homogeneous membrane particles of endocytic origin ranging in size from 40 to 100 nm, microvesicles are directly shed from the plasma membrane into the extracellular environment representing a larger and heterogeneous population with 50 to 1000 nm in diameter [49]. Although both types of microparticles differ in size, origin and releasing mechanism, exosomes and microvesicles contain a large panel of proteins, functional mRNAs and regulatory microRNAs (miRs) which contribute to the cellular interplay between MSC and cancer cells within the tumor microenvironment and thereby altering the functionality of recipient cells [37]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous results demonstrated that MSC-derived exosomes can modulate the function of tumor cells by induction of MMP-2 and ecto-5’-nucleotidase activity resulting in a more complex tumor microenvironment with higher tumor heterogeneity [37, 50]. Alternatively, MSC-derived exosomes also contain tumor supportive miRs which enhance tumor growth in vivo [51].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the common surface markers of exosomes (CD9 and CD81), MSC-DEs express several molecules of MSCs, such as CD29, CD44, CD90 and CD73. 51,52 In addition to proteins, exosomes are enriched with a collection of cytokines, certain lipid rafts such as phosphoglycerides, cholesterol, ceramide, fatty-acyl chains as well as mRNAs, miRNAs, non-coding RNAs, tRNAs, rRNAs and rarely DNA. 35 …”
Section: Exosomesmentioning
confidence: 99%
“…As previously discussed, tumor cells can modify the surrounding cells, inducing protumorigenic phenotypes. This bidirectional crosstalk is partly mediated by EVs originating from both the MSCs and tumor cells, as shown by Yang et al (115) (Figure 3). Peinado et al (116) showed that tumor cells can modify bone marrow cells, promoting recruitment and "educating" them toward a pro-vasculogenic and prometastatic phenotype.…”
Section: Factors Associated With the Dual Role Of Mscevs In Tumorsmentioning
confidence: 76%